2014
DOI: 10.1177/0218492314538844
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic versus catheterization angiography in tetralogy of Fallot

Abstract: For preoperative evaluation of tetralogy of Fallot patients, multidetector computed tomographic angiography can be used as a reliable noninvasive alternative to cardiac catheterization angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…10 Garg et al, studied the MDCT vs. CCA in CHD diagnosis and found few small VSDs were missed on MDCT. 9 These findings correlate with our study. In this study, we found 9 patients (18%) of ASD without other anomalies like pulmonary stenosis, MPA, TOF, and other pathologies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…10 Garg et al, studied the MDCT vs. CCA in CHD diagnosis and found few small VSDs were missed on MDCT. 9 These findings correlate with our study. In this study, we found 9 patients (18%) of ASD without other anomalies like pulmonary stenosis, MPA, TOF, and other pathologies.…”
Section: Discussionsupporting
confidence: 92%
“…8 Garg et al, studied the MDCT vs. CCA in diagnosing TOF and found 100% sensitivity, specificity and accuracy. 9 Complete concordance between the diagnosis of RVOT, pulmonary artery anatomy, pulmonary annulus size, side of aortic arch and detection of collaterals was found. In this study, we found 36 (72%) patients of VSD without other anomalies like pulmonary stenosis, MPA, TOF, and other pathologies.…”
Section: Discussionmentioning
confidence: 64%
“…These findings are similar to reported clinical series [15, 16]. Anomalous coronary arteries are at risk of transection during complete repair, especially if mistaken for a large infundibular or conal branch [17]. There is no consensus on how to deal with such anomalous coronary arteries.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, DSCT was performed strictly in accordance with the ALARA (as low as reasonably achievable) principle in the present study. It is worth noting that several measures were applied to minimize the estimated mean ED to < 1 mSv (0.86 ± 0.47 mSv), which is much lower than that of CCA (approximately 4.6 mSv) [ 21 , 22 ], including decreasing the tube voltage to the low level of 80 kV, applying the heart rhythm adaptive pitch, and using ECG-based tube current modulation as shown in previous studies [ 23 – 25 ].…”
Section: Discussionmentioning
confidence: 99%